Self–efficacy and student satisfaction in the context of blended learning courses. (3rd April 2022) - Prifti, Rezart
ABSTRACT: Higher education institutions are increasingly looking for the adoption of new ways to improve education quality, enhance student engagement, and manage knowledge resources. Technological developments have a significant impact on education, and technology-mediated learning is steadily progressing, with blended learning being implemented in education institutions. This article focuses on student satisfaction resulting from the introduction of a blended course, which was implemented in a 'Management' course, in university premises. In particular, we investigate Learning Management System (LMS) factors that affect its self-efficacy and the impact it has on student satisfaction. The results show that LMS self-efficacy positively impacts students' satisfaction with their education. Moreover, we identify the content of the system, system accessibility, and system components related to the enhancement of critical thinking, to be important determinants of LMS self-efficacy.